Employee Performance, Socialization, and Job Satisfaction Are Influenced by the Independent Variable of Work-Life Balance: Community Service - Agus Setiawan; Yogi Ashari; Deni Priansyah; Soma Ariyaka; Taufik Mr; Ali Sumara El Khomeiny (Siber Nusantara Research, 2026)
This Community Service activity was conducted with the aim of increasing participants' knowledge and awareness regarding the role of work-life balance and its relationship to employee performance and job satisfaction. The activity was held online on October 8, 2025, via Zoom Meeting by STEKOM Semarang University. A total of 74 participants, consisting of students, recent graduates, educators, and employees from various fields, participated in this activity. The implementation method used was a socialization combined with discussions and interactive Q&A sessions to encourage active participant involvement. The results of the activity showed an increase in participants' understanding of the concept of work-life balance and its impact on performance and job satisfaction. Participants were able to identify various obstacles in maintaining a balance between work and personal life demands, while also understanding the importance of time management, mental health, and work role limitations. Furthermore, this activity fostered participants' motivation to begin implementing work-life balance principles in their daily work and academic activities. Overall, this community service activity had a positive impact in raising awareness of the importance of work-life balance as a supporting factor for optimal and sustainable performance and job satisfaction.